Development of Canva Aplication based E-Magazine on Static Fluids to Improve Student Motivation - Gunawan, Cahya Widya; Risdianto, Eko; Putri, Desy Hanisa (Kasuari: Physics Education Journal (KPEJ), 2022)
This study aims to test the feasibility of E-magazine learning media on static fluid materials to increase student motivation. This research method is ADDIE development model. The assessment instrument used in this study was an expert validation sheet which consisted of content aspects, presentation aspects, linguistic aspects, media aspects and motivational aspects and student perception sheets which consisted of several aspects, namely, material aspects, language aspects, and media aspects. Based on the results of expert validation from. Based on the results of the product validation test, the validator gets an overall average percentage of 86.92% with a very decent category. Based on the results of students' perceptions of the E-magazine, it can be said to be very good in the three Schools, with an overall average percentage of 87.22%. So it can be concluded that learning media products based on E-magazines on static fluid material to increase student learning motivation are very feasible to use.